2016
DOI: 10.3390/su9010051
|View full text |Cite
|
Sign up to set email alerts
|

Economic Assessment of Overtopping BReakwater for Energy Conversion (OBREC): A Case Study in Western Australia

Abstract: This paper constructs an optimal configuration assessment, in terms of the financial returns, of the Overtopping BReakwater for wave Energy Conversion (OBREC). This technology represents a hybrid wave energy harvester, totally embedded in traditional rubble mound breakwaters. Nine case studies along the southern coast of Western Australia have been analysed. The technique provides tips on how to estimate the quality of the investments, for benchmarking with different turbine strategy layouts and overlapping wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 69 publications
0
35
0
Order By: Relevance
“…There are of course various reasons why this is the case-in the first place the already mentioned limitations due to the model's inherent limits [38][39][40]; a further practical reason is the effect, also discussed above, caused by the longer sampling time of the model data in comparison with the high data sampling of modern wave buoys (30 ), which also coincide with the standard engineering practice.…”
Section: Discussionmentioning
confidence: 99%
“…There are of course various reasons why this is the case-in the first place the already mentioned limitations due to the model's inherent limits [38][39][40]; a further practical reason is the effect, also discussed above, caused by the longer sampling time of the model data in comparison with the high data sampling of modern wave buoys (30 ), which also coincide with the standard engineering practice.…”
Section: Discussionmentioning
confidence: 99%
“…Rusu and Soares have indicated that actual wave power yield depends on the particular WEC device as rated by its wave power generation because each technology has different operational ranges and different efficiencies under various sea states [37]. Contestabile et al constructed an optimal configuration assessment in terms of the financial returns of the Overtopping BReakwater for wave Energy Conversion (OBREC) [38]. Vannucchi and Cappietti assessed the performances of 6 state-of-the art WECs in Italian nearshore waters [39].…”
Section: ) Overall Condition Analysis For Wave and Wind Energymentioning
confidence: 99%
“…Thanks to site-specific turbine strategy, including several pico turbines (<5 kW) or a combination of pico and micro turbines (<100 kW), OBREC works with a wide spectrum of different incident wave conditions and water levels. The device tends to be most effective in mild and poor wave climates [23][24][25][26].…”
Section: Overtopping Breakwater For Wave Energy Conversionmentioning
confidence: 99%